Foreign clouds in the European sky: how US laws affect the privacy of Europeans - Primavera De Filippi (Internet Policy Review, 2013)
This article presents a general analysis of how user autonomy in the cloud is increasingly put into jeopardy by the growing comfort and efficiency of the user-interface. Although this has not been, thus far, explicitly addressed by the law, it is a fundamental ethical question that should be carefully assessed to guide the future deployment of cloud computing. Different policy decisions might, in fact, significantly affect user's fundamental rights and online freedoms by shifting the balance from one part or another of the trade-off. This article aims to explore emerging trends in cloud computing technologies and analyse them from an ethical perspective to identify the issues they might raise, and the extent to which current laws and regulations actually take these issues into account.
Keywords: 300; Foreign Intelligence Surveillance Amendments Act (FISAA); USA Patriot Act; EU Data Protection Regulation; Data sovereignty; EU Cybersecurity Directive; Cloud services; Cloud